Definition and use of Solution-focused Sustainability Assessment: A novel approach to generate, explore and decide on sustainable solutions for wicked problems. (May 2016) - Zijp, Michiel C.; Posthuma, Leo; Wintersen, Arjen; Devilee, Jeroen; Swartjes, Frank A.
Abstract: This paper introduces Solution-focused Sustainability Assessment (SfSA), provides practical guidance formatted as a versatile process framework, and illustrates its utility for solving a wicked environmental management problem. Society faces complex and increasingly wicked environmental problems for which sustainable solutions are sought. Wicked problems are multi-faceted, and deriving of a management solution requires an approach that is participative, iterative, innovative, and transparent in its definition of sustainability and translation to sustainability metrics. We suggest to add the use of a solution-focused approach. The SfSA framework is collated from elements from risk assessment, risk governance, adaptive management and sustainability assessment frameworks, expanded with the 'solution-focused' paradigm as recently proposed in the context of risk assessment. The main innovation of this approach is the broad exploration of solutions upfront in assessment projects. The case study concerns the sustainable management of slightly contaminated sediments continuously formed in ditches in rural, agricultural areas. This problem is wicked, as disposal of contaminated sediment on adjacent land is potentially hazardous to humans, ecosystems and agricultural products. Non-removal would however reduce drainage capacity followed by increased risks of flooding, while contaminated sediment removal followed by offsite treatment implies high budget costs and soil subsidence. Application of the steps in the SfSA-framework served in solving this problem. Important elements were early exploration of a wide 'solution-space', stakeholder involvement from the onset of the assessment, clear agreements on the risk and sustainability metrics of the problem and on the interpretation and decision procedures, and adaptive management. Application of the key elements of the SfSA approach eventually resulted in adoption of a novel sediment management policy. The stakeholder participation and the intensive communication throughout the project resulted in broad support for both the scientific approaches and results, as well as for policy implementation. Graphical abstract: Highlights: Solution-focused Sustainability Assessment (SfSA) is introduced and defined. SfSA explores stakeholder and science supported solutions for wicked problems. SfSA considers multi-faceted people, planet, and profit metrics. The focus on multiple solutions improves the utility of the assessment results. The utility of SfSA is illustrated with a case study on sediment management.